Drinkers' identification with varying alcohol consumption prototypes - Pettigrew, Simone; Jongenelis, Michelle; Pratt, Steve; Slevin, Terry; Chikritzhs, Tanya (Wiley-Blackwell Publishing Ltd., 2017)
Introduction and Aims: Efforts to reduce excessive alcohol consumption need to take into account drinkers' perceptions of their risk of alcohol-related harm. The aim of the present study was to profile adult Australian drinkers according to their self-identification with various drinker prototypes to determine the extent to which these prototypes are associated with perceived and actual risk of alcohol-related harm. Design and Methods: A large web panel provider disseminated an online survey to a national sample of 2168 drinkers aged 18+years who consumed alcohol at least twice per month. Respondents reported whether they considered themselves to be a light, occasional, social, heavy or binge drinker. The nominated category was compared with perceived and actual risk of alcohol-related harm. Results: The prototype most commonly nominated by respondents was 'social drinker' (45%), and the least common was 'binge drinker' (7%). Although the heaviest drinkers in terms of actual reported consumption typically selected prototypes indicative of harmful consumption, many of those selecting prototypes indicative of moderate consumption were at risk of alcohol-related harm. Discussion and Conclusions: Many adult drinkers may be unaware of their risk of alcohol-related harm. The results suggest that there may be a need to recalibrate Australian drinkers' perceptions of high-risk drinking.